2021
DOI: 10.21203/rs.3.rs-1175984/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does the Addition of Cellulosic Micro/nanofibrils Improve the Properties of Hydroxypropyl Methylcellulose Films?

Abstract: Damages to ecosystems, due to the consumption of petroleum-based materials, can be mitigated with the use of biopolymers such as cellulose derivatives. The objective was to evaluate the influence of different proportions of cellulose micro/nanofibrils (MFC/NFC) on the properties of hydroxypropyl methyl cellulose (HPMC) films. Films were prepared using proportions of 0, 25, 50, 75 and 100% (w/w) of MFC/NFC of Pinus sp. in relation to HPMC. The physical, barrier, surface, optical, morphological and mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 91 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…MFC is composed of high-aspect-ratio nanosized fibrils in the 10-100 nm range. It is characterized by a high specific surface area and a large number of surface hydroxyl groups which can generate inter-and intramolecular hydrogen bonds [22,23]. Briefly, MFC is obtained by mechanical or chemical destruction of the multilevel organization of natural fibers in cellulose and then extraction of the microfibrils [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MFC is composed of high-aspect-ratio nanosized fibrils in the 10-100 nm range. It is characterized by a high specific surface area and a large number of surface hydroxyl groups which can generate inter-and intramolecular hydrogen bonds [22,23]. Briefly, MFC is obtained by mechanical or chemical destruction of the multilevel organization of natural fibers in cellulose and then extraction of the microfibrils [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Fotie et al reported using MFC as a coating for food packaging plastics, whereas changes in the oxygen barrier properties were observed [27]. Furthermore, MFC can be successfully used for the development of coatings for paper packaging [22]. Wei et al investigated starch-corn stalk cellulose material for biodegradable straws [28] instead of plastic straws, which are restricted in UE.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed to use an alcohol gel formulation from mechanically de brillated nano cellulose (MFC), as it is cheaper than existing products, has forestry origin, is affordable, and is available on a large scale [8]. The importance increases due to the accumulation of petroleum products that causes damage to ecosystems, which can be avoided with cellulose-based products [9], which could be minimized with cellulose-based products [10,11]. However, in this crop, there is a particular concern with an insect attack denominated Leptocybe invasa pest Fisher & La Salle 2004 (Hymenoptera: Eulophidae), known as eucalyptus gall wasp [12].…”
Section: Introductionmentioning
confidence: 99%